Acquired chylothorax in association with supraclavicular ultrasound-guided access to the brachiocephalic vein in a neonate. Issue 4 (July 2022) - Zhong, Bella; Barnes, Richard; Malhotra, Atul; Pharande, Pramod
Achieving and maintaining venous access can be challenging in some premature and low birth weight infants. In this population, the supraclavicular ultrasound-guided in-plane approach to the brachiocephalic vein for central venous access has demonstrated great success with a low rate of complications. This case describes the first report of acquired chylothorax in association with this technique, in a previously extremely preterm and low birth weight infant.